2009
DOI: 10.1128/ec.00030-09
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Mutant Form of EhRabA, a Unique Rab GTPase of Entamoeba histolytica , Alters Endoplasmic Reticulum Morphology and Localization of the Gal/GalNAc Adherence Lectin

Abstract: Entamoeba histolytica is a protozoan parasite that causes amoebic dysentery and liver abscess. Vesicle trafficking events, such as phagocytosis and delivery of plasma membrane proteins, have been implicated in pathogenicity. Rab GTPases are proteins whose primary function is to regulate vesicle trafficking; therefore, understanding the function of Rabs in this organism may provide insight into virulence. E. histolytica possesses a number of unique Rabs that exhibit limited homology to host Rabs. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…histolytica expression vector pGIR209, which confers G418 (neomycin) resistance and allows for tetracycline-inducible expression of exogenous genes [20]. A standard electroporation protocol [21] was utilized to introduce the expression vector into trophozoites that had been previously transfected with another plasmid, pGIR308. This partner plasmid encodes the tetracycline repressor protein, which is necessary for tetracycline inducibility.…”
Section: Resultsmentioning
confidence: 99%
“…histolytica expression vector pGIR209, which confers G418 (neomycin) resistance and allows for tetracycline-inducible expression of exogenous genes [20]. A standard electroporation protocol [21] was utilized to introduce the expression vector into trophozoites that had been previously transfected with another plasmid, pGIR308. This partner plasmid encodes the tetracycline repressor protein, which is necessary for tetracycline inducibility.…”
Section: Resultsmentioning
confidence: 99%
“…Expression from this plasmid is driven by upstream ferredoxin regulatory sequences. The cDNA library in pAH-DEST was transfected into HM1: IMSS trophozoites using standard protocols (10,29). Transfectants were maintained by the addition of 23 g/ml hygromycin to the medium.…”
Section: Methodsmentioning
confidence: 99%
“…histolytica trophozoites were transfected with expression plasmids encoding SREHP or EhCoactosin using standard transfection protocols (10,29). These 2nd-generation SREHP and EhCoactosin overexpressors were maintained in a medium supplemented with 23 g/ml hygromycin, and the drug concentration was increased to 46 g/ml for 1 week prior to conducting experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Although the secretory/endocytic pathway is not well characterized in Entamoeba histolytica, it has been shown that fibronectin receptor and Gal/GalNAc lectin trafficking to plasma membrane is brefeldin-A-dependent, whereas thiolproteinase secretion is brefeldin-A-independent in this parasite (33). Further characterization reveals that overexpression of a GTP-locked mutant of EhRabA alters ER morphology and mislocalizes Gal/GalNAc lectin without affecting the localization of other cell surface proteins, indicating the specific role of EhRabA in early secretory pathway (34). Bioinformatic analyses have shown the presence of a Rab1 homologue in Giardia lamblia (35), Plasmodium falciparum (36), and Leishmania major (37); however, the functional role of Rab1 in the secretory pathway of these parasites is not yet elucidated.…”
mentioning
confidence: 98%